Albuminuria: Prevalence, associated risk factors and relationship with cardiovascular disease. Issue 4 (28th November 2013) - Chen, Fang; Yang, Wenying; Weng, Jianping; Jia, Weiping; Ji, Linong; Xiao, Jianzhong; Shan, Zhongyan; Liu, Jie; Tian, Haoming; Ji, Qiuhe; Zhu, Dalong; Ge, Jiapu; et al.
Abstract Aims/Introduction To investigate the prevalence and associated risk factors of microalbuminuria, and to explore the relationship between albuminuria and cardiovascular disease (CVD). Materials and Methods A nationally representative sample of 38, 203 Chinese participants was categorized by different levels of urinary albumin‐to‐creatinine ratio (ACR; 0 –10 mg/g, 10 –20 mg/g, 20 –30 mg/g, 30 –300 mg/g). The prevalence of albuminuria was compared by using a single urinary ACR cut‐off point and by sex‐specific ACR cut‐off points. Factors associated with the presence of albuminuria, and the relationship between albuminuria and CVD were analyzed by logistic regression. Results Prevalence of albuminuria as measured by a single ACR cut‐point was significantly lower for men compared with women (13.9% vs 19.1% in the normal glucose tolerance group; 20.8% vs 26.8% in the impaired glucose tolerance group, P < 0.01). The prevalence of albuminuria, as measured by sex‐specific ACR cut‐points, was higher for men than women (31.4% vs 29.6% in the normal glucose tolerance group; 42.2% vs 39.3% in the impaired glucose tolerance group, P < 0.01). The independent risk factors for the presence of albuminuria were aging, female sex, hypertension, hyperglycemia, obesity, dyslipidemia, insulin resistance and metabolic syndrome. The subdivided normal ACR group did not show a linear or statistically significant relationship with CVD after adjusting for conventional CVD risk factors (P > 0.05). Conclusions The prevalence of albuminuria was high in the general Chinese population. Aging, female sex, hypertension, hyperglycemia, dyslipidemia, insulin resistance, obesity and metabolic syndrome were all independent risk factors for albuminuria. The causal relationship between ACR and CVD might require further follow‐up investigation.